Separate units for incarcerated people who committed sexual offenses: luxury or necessity? - Wuyts, Elise; De Boeck, Minne; Dilliën, Tineke; Merckx, Liesbeth; Uzieblo, Kasia; De Koster, Katrien; De Schutter, Astrid; Goethals, Kris (Frontiers in Psychiatry, 2023)
Introduction The policy on treatment of people who commit sexual offenses (PSOs) varies greatly across countries, creating different treatment environments. This study was conducted in Flanders (i.e., the Dutch-speaking part of Belgium) where PSOs receive their treatment in the community. Before this transfer takes place, many PSOs spend time inside prison together with other offenders. This raises the question to what extent PSOs are safe in prison and whether this period would benefit from an integrated therapeutic program. This qualitative research study focuses on the possibility of separate housing for PSOs by examining the current experiences of incarcerated PSOs and contextualizing those with the professional experience of national and international experts in the field. Methods Between 1 April 2021 and 31 March 2022, 22 semi-structured interviews and six focus groups took place. Participants were comprised of 9 imprisoned PSOs, 7 international experts on prison-based PSO treatment, 6 prison officer supervisors, 2 prison management delegates, 21 healthcare workers (both inside and outside prison), 6 prison policy coordinators, and 10 psychosocial service staff members. Results Nearly all interviewed PSOs reported suffering at the hands of fellow inmates or prison staff because of the nature of their offenses, varying from exclusion and bullying to physical violence. These experiences were corroborated by the Flemish professionals. Consistent with scientific research, the international experts all reported working with incarcerated PSOs who reside in living units separate from other offenders and the therapeutic benefits to this approach. Despite this growing evidence, the Flemish professionals remained reluctant to implement separate living units for PSOs in prisons because of the perceived risk of increased cognitive distortions and further isolation of this already stigmatized group. Conclusion The Belgian prison system is not currently organized to create separate living units for PSOs, which has important ramifications for the safety and therapeutic opportunities of these vulnerable prisoners. International experts emphasize a clear benefit for introducing separate living units where a therapeutic environment can be created. Although this would have significant organizational and policy-oriented implications, it would be useful to explore whether these practices could be implemented in Belgian prisons as well.